THE ROLE OF RONDO TRAINING IN IMPROVING THE PASSING ACCURACY OF U 15 SSB TALENTA ACEH FOOTBALL ATHLETES - Hariansyah, Septi; Irwandi, Irwandi; Munzir, Munzir; Fajrial, Jul (Sport Pedagogy Journal, 2025)
This study aims to analyze the role of rondo training in improving the passing accuracy of U-15 athletes at SSB Talenta Aceh Football. The method used in this study was an experiment involving 15 athletes who underwent a passing accuracy test before and after an 8-week rondo training program. The data obtained showed that the average pretest score before training was 8.93, while the average postes score after training increased to 11.47. Statistical analysis showed a standard deviation of 1,580 for pretes and 1,187 for postes, signaling an increase in performance consistency. The hypothesis test yielded a t-value of 5.824, which showed that the difference between the pretest and postes scores was significant. These findings indicate that rondo training not only improves passing accuracy but also has a positive impact on athletes' confidence and adaptability in game situations. The results of this study recommend the application of the rondo training method regularly in the training program to support the development of technical skills of young athletes. Thus, rondo training can be an effective strategy in improving football performance among U-15 athletes at SSB Talenta Aceh Football.Keywords: rondo training, passing accuracy, SSB Talenta Aceh FootballKeywords: Rondo Training, Passing Accuracy, SSB Talenta Aceh Football